European Identity in Russian Regions Bordering on Finland: Quantitative Analysis - A. O. Domanov (Сравнительная политика)
Th e quantitative analysis of an opinion poll conducted in October 2013 in three Russian cities located near Finnish border (St-Petersburg, Kronstadt and Vyborg) explores European identity of their citizens. Th is area was chosen to illustrate the crucial importance of space interpretation in spatial identity formation by using critical geopolitical approach. Th e study shows how diff erent images of space on the same territory act as intermediate variables between objective territorial characteristics and citizens’ identities. As the geographical position at the border of Russia provides the citizens with geopolitical alternatives to identify their location as a fortress defending the nation (as in the case of Kronstadt) or a bridge between cultures, the given study allows us to compare reasons for these geopolitical choices of inhabitants. Furthermore, the research aims at bridging the gap in the studies of European and multiple identity in Russian regions and provides Northwest Russian perspective on the perpetual discussion about subjective Eastern border of Europe.